Effect of Thyroid Disorders on Cardiovascular Risk in Type 2 Diabetes Mellitus Patients - Mushtaq , Furqan; Aqsa Amjad,; Qureshi , Maryam Junaid; Aisha Butt,; Ahmad , Mansoor; Haider , Hafiz Muhammad Ali; Ali Raza, (Indus Journal of Bioscience Research, 2025)
Introduction: Thyroid disorders and type 2 diabetes mellitus (T2DM) are two interlinked endocrine conditions that frequently coexist. Emerging evidence suggests that thyroid dysfunction may exacerbate cardiovascular risks in T2DM patients by influencing lipid metabolism, insulin sensitivity, and vascular health. Objective: To evaluate the impact of thyroid disorders, including hypothyroidism and hyperthyroidism, on cardiovascular risk profiles in patients with type 2 diabetes mellitus. Methodology: This study examined the relationship between thyroid function and cardiovascular risk in patients with type 2 diabetes mellitus at Shalamar Hospital, Lahore, during July to December 2024. A total of 175 participants met the inclusion criteria, ensuring reliable thyroid function assessments. Data collection involved thyroid function tests, lipid profiles, blood pressure monitoring, and echocardiographic evaluations. Statistical analysis using SPSS v26 included descriptive statistics, t-tests, and chi-square tests, with significance set at p<0.05. The study’s findings contribute to understanding the impact of thyroid function on cardiovascular health in diabetic patients, potentially aiding in better disease management and risk stratification strategies. Results: Thyroid dysfunction affected 40% of patients, with hypothyroidism (25%) being most common. Patients with thyroid disorders showed higher LDL (135 mg/dL vs. 100 mg/dL), triglycerides (180 mg/dL vs. 140 mg/dL), arterial stiffness (60% vs. 35%), and systemic inflammation (CRP 6.5 mg/L vs. 3.8 mg/L). Glycemic control was poorer, with HbA1c 8.2% vs. 7.5%, highlighting increased cardiovascular risk in this population. Conclusion: Thyroid dysfunction is a significant modifiable risk factor for cardiovascular complications in T2DM patients. Early detection and management of thyroid disorders could mitigate cardiovascular risks and improve overall outcomes.